Students’ Behavioral Engagement in Learning English in Vocational High School - elguanda, andhara suci; Siska, S. S; Rika AFRIYANTI (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The purpose of this study was to analyze student behavioral engagement about how students' behavior is related to academic assignments in tenth and twelfth grade of SMK N 1 Muara Bungo. So that students are interested in doing English assignments. in class X & XII SMK N 1 Bungo. The design of this research is descriptive qualitative. The sample of this research is class X AKL & XII MM2. The instruments used in this study were observation, using an observation checklist, field notes and videos. The results of this study are classified into three forms: persistence, focus, asking questions, contributing to class discussion. Based on the results of this study the researcher found that students gave persistence when studying but there were some students who were not too effort in doing task because of the lack of previous knowledge about English, but they only showed an attitude of wanting to do the task and were interested in doing it but not by showing persistence because of the assignment. given by the teacher aspects that are assessed mostly from the creativity of students in designing. But in class students can be focused and contribute in class discussions, such as asking questions about instructions and focusing on doing assignments.